Working environment and employee job performance in GSIS-Iloilo City - Armada, Ullyn; Cervas, kristine; Elesis, Treena; Near, Meg.; Sumogat, Jamille; Tornalejo, Norlene; Verdadero, Kaila (2015.)
The study uses a qualitative approach in describing the job performance, working environment and level of employee productivity in GSIS, Iloilo City. The conceptual framework was used as basis of an interview schedule that was given to GSIS-Iloilo employees. Primary data was obtained through surveys conducted among the management and employees of GSIS-Iloilo who were randomly selected from different divisions. In terms of job performance, the respondents rated themselves to be fairly effective considering the physical environment of their workplace. The employee also have a good relationship with their co-workers, which in turn result to a better performance of assigned tasks. The employees' good job performance can also be manifested through their attendance and punctuality. Majority of the employees have minimal tardiness and absenteeism, which shows their positive attitude towards their job. As far as work environment is concerned, the employees responded with positive feedback. They have little complaints with regards to the physical layout of their work place and they are provided with equipment that would make their jobs easier. This may be the reason why the employees are comfortable in their workplace, having no ergonomic problems that could disrupt their workflow. In line with this, the organization also provides the employees with a clear description of their responsibilities and they also have supervisors who would guide them if ever they encounter difficulties. With this comes employee empowerment that would produce employees with holistic personal and professional development. Lastly, results for the level of employee productivity in GSIS-Iloilo show that the organization gives importance in achieving a superior quality of service through improving client relation and employee job satisfaction
Research Paper (Mgt 199-Management Research). -- [Iloilo City] : University of the Philippines in the Visayas-College of Management, December 2015.